The Role of Budget Deficit in the Economic Growth of Pakistan (Global Journal of Management and Business Research, 2013)
The basic aim of this paper is to investigate the relation between Budget Deficit and Gross Domestic Product of Pakistan. There are three views about this relation. Keynesian says that there is a positive relation between budget deficit and economic growth while neo-classical views that there is an inverse relation between budget deficit and economic growth. Recardian says that there is neutral relation between budget deficit and economic growth. A time series data for the period of 1971-2007 has been used to check the relation between budget deficit and economic growth of Pakistan. GDP is taken as dependent variable, FDI and budget deficit as independent variables. ADF test has been used to check the stationary of the data. All variables get stationary at 5% level of significance at level. The results of Granger causality test show that there is bi-directional causality running from budget deficit to GDP and GDP to budget deficit.
Keywords: GDP; budget deficit; OLS; Pakistan